Uwarunkowania doboru modelu wyceny aktywów jednostki gospodarczej - Rówińska, Małgorzata (The conditions of choice asset valuation models, 2008)
Polish and international law of accounting indicates two models of valuation assets. The first model is historical cost model, the second one is fair value model. This is an accounting convention (particularly international accounting) which departs from historical cost to recognize the increased value of assets. The resulting gains or losses are reflected either in the profit and loss account immediately or taken to equity (and recognized later in the profit and loss account upon disposition).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 404-412